Characterization of a WaaF (RfaF) Homolog Expressed by Haemophilus ducreyi - Bauer, Beth A. (American Society for Microbiology, 1999)
Haemophilus ducreyi lipooligosaccharide (LOS) is capable of inducing an inflammatory response in skin (A. A. Campagnari, L. M. Wild, G. Griffiths, R. J. Karalus, M. A. Wirth, and S. M. Spinola, Infect. Immun. 59:2601–2608, 1991) and likely contributes to the virulence of this sexually transmitted pathogen (B. A. Bauer, M. K. Stevens, and E. J. Hansen, Infect. Immun. 68:4290–4298, 1998). An open reading frame in H. ducreyi 35000 was found to encode a predicted protein that was 59% identical to the protein product of the rfaF (waaF) gene of Salmonella typhimurium. The H. ducreyi waaF gene was able to complement an S. typhimurium rfaF (waaF) mutant, a result which confirmed the identity of this gene. In contrast to the rfaF (waaF) gene of enteric bacteria, the H. ducreyi waaF gene was not located adjacent to other genes involved in lipopolysaccharide expression. Inactivation of the H. ducreyi waaF gene by insertion mutagenesis resulted in expression of a LOS that migrated much faster than wild-type LOS in sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The LOS of this mutant also did not bind a monoclonal antibody directed against a cell surface-exposed epitope of wild-type H. ducreyi LOS. Testing of the wild-type H. ducreyi strain and its isogenic waaF mutant in the temperature-dependent rabbit model for dermal lesion production by H. ducreyi revealed that this waaF mutant was less virulent than the wild-type parent strain. Complementation of the H. ducreyi waaF mutant with the wild-type H. ducreyi waaF gene resulted in expression of both wild-type LOS and wild-type virulence by this mutant.